The matter of revolution : science, poetry, and politics in the age of Milton - Rogers, John, 1961- (Book collections on Project MUSE., 1996)
John Rogers addresses the literary and ideological consequences of the remarkable, if improbable, alliance between science and politics in seventeenth-century England. He looks at the cultural intersections between the English and Scientific Revolutions, concentrating on a body of work created in a brief but potent burst of intellectual activity during the period of the Civil Wars, the Interregnum, and the earliest years of the Stuart Restoration. Rogers traces the broad implications of a seemingly outlandish cultural phenomenon: the intellectual imperative to forge an ontological connection between physical motion and political action. The work of the writers whom Rogers discusses - John Milton, Andrew Marvell, Gerrard Winstanley, William Harvey, and Margaret Cavendish - spans the spectrum of genres from medical treatise to epic poem. Despite their differences, each text participates in or reacts to one of the least understood intellectual movements in early modern England, a short-lived embrace of philosophical idealism that Rogers identifies as the Vitalist Moment. Each writer, he asserts, struggled to reconcile the new materialist science of corpuscular motion and interaction with the new political philosophy of popular sovereignty and consensus.